Approach to syncope in the elderly - ERDOĞAN, OKAN (TURKISH SOC CARDIOLOGY, 2017)
Elderly syncope currently accounts a substantial number of emergency admissions. Unfortunately, in elderly syncope we are faced with major difficulties while providing diagnostic and therapeutic decisions. It is quite necessary to distinguish between syncope and non-syncopal causes which create further difficulties during diagnostic work-up because of co-morbid conditions and poly-pharmacy used by the elderly. The present article aims to describe causes of elderly syncope and its differential diagnosis as well as tips and tricks during diagnostic process.
Keywords: Arrhythmia; loss of consciousness; syncope; elderly; PATIENT